Music Learning Strategies Through the Beyond Center and Circle Time (BCCT) Approach at Bosowa Natural School Makassar (SABM) - M. Marauna, Vikran; Utomo, Udi; Wadiyo, Wadiyo (Catharsis, 2019)
Music learning at the Bosowa Natural School Makassar (SABM) uses the Beyond Center and Circle Time (BCCT) learning model as a strategy for achieving the expected learning objectives of music. Besides learning music in SABM is an intra-curricular subject that must be taught to students because SABM refers to one of multiple intelligences, namely musical intelligence. Therefore, this study aims to analyze music learning through the BCCT approach. The method used in this research is interpretative qualitative with an interdisciplinary approach. Data was collected through observation, interviews, and documentation studies with interactive model analysis. The results showed (1) the environmental footing gave rise to learning activities in the making of learning media which were implemented by the demonstration method, (2) the footing before learning, singing could build the mood of students, and embed the value of knowledge through song lyrics, (3) the footing during learning, the lecture method, question and answer, and drill practice are very effective for students to better understand theory and practice, (4) footing after learning, train students to speak according to what has been passed from the beginning to the end of learning while practicing memory, patience, and respect.